DEVELOPMENT OF A SELF-ASSESSMENT-BASED COLLABORATION ASSESSMENT INSTRUMENT ON CONSTRUCTION AND HOUSING PLANNING - Mita Sofia; Sri Sumarni; Fajar Danur Isnantyo; Vernanda Atik Dewi Sasanti; Diva Jaira Arlesa; Fahrudin Ali Fikri; Fadia Husna Nabila (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: It developed a collaborative assessment tool to allow students to evaluate their abilities. This research is a research and development (R&D) using the ADDIE stage approach. The development of the laboratory instrument is made in the form of a non-test self-assessment sheet. The experiential team assesses the validity of the data in the fields of materials, construction, and language. The Aiken equation with the coefficient V Aiken is used as a decision rule in determining the instrument's validity. This study interviewed five experts and 34 vocational high school students in Surakarta. The results showed that the self-assessment-based assessment instrument was valid, reliable, and suitable for vocational students. Abstract: Penelitian ini mengembangkan perangkat penilaian kolaborasi yang bertujuan memberikan kesempatan siswa mengevaluasi kemampuan dirinya sendiri. Penelitian ini merupakan reseach dan development (R&D) menggunakan pendekatan tahapan ADDIE. Pengembangan instrumen kolaborasi dibuat dalam bentuk lembar penilaian diri non tes. Validitas data dinilai oleh tim ekspert di bidang materi, konstruksi, dan bahasa. Persamaan Aiken dengan koefisien V aiken digunakan sebagai kaidah keputusan dalam menentukan validitas instrumen. Dalam penelitian ini melibatkan 5 orang ahli dan 34 siswa SMK di Surakarta sebagai responden penelitian. Hasil penelitian menunjukkan bahwa instrumen penilaian kolaborasi berbasis self assessment telah valid dan reliabel sehingga layak digunakan untuk siswa kejuruan.